Organic wastewater treatment agent and preparation method thereof
The organic wastewater treatment agent produced by reacting modified cellulose with functionalized nanosilica uses its adsorption and bactericidal ability to solve the degradation problem of difficult-to-degrade organic wastewater, and achieves efficient pollutant adsorption and degradation effects.
Patent Information
- Application Number
- CN202411566063.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art is difficult to effectively degrade the difficult-to-degrade organic wastewater generated in industrial production, especially due to its complex composition, high toxicity and stable chemical structure, it is difficult to be degraded by microorganisms, resulting in challenges in environmental protection.
The organic wastewater treatment agent is prepared by reacting modified cellulose with functionalized nanosilica, and the adsorption ability of cationic pollutants and quaternary ammonium salts of modified nanosilica is used to absorb phosphate anions of cationic pollutants and quaternary ammonium salts, as well as the bactericidal effect of thiourea. Combined with organic frameworks to decompose organic pollutants in photocatalytic degradation.
It has achieved efficient degradation of difficult-to-degrade organic wastewater and adsorption and bactericidal effects of pollutants, significantly improving the degradation ability of water treatment agents and pollutant adsorption ability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of water treatment materials, in particular to an organic wastewater treatment agent and a preparation method thereof. Background Art
[0002] Water treatment agent is a general term for a class of chemical agents used for water treatment. It is mainly used to remove harmful substances in water, such as corrosives, metal ions, dirt and microorganisms, in order to obtain civil or industrial water that meets the requirements. Water treatment agent is an important category of fine chemical products with strong specificity. Different water treatment agents are required for different purposes and treatment objects.
[0003] The rapid development of industrialization has put the economic development level on the fast track. Chemical wastewater is generated in industrial production, and this type of wastewater contains a large amount of difficult-to-degrade organic matter. Refractory organic pollutants have the characteristics of complex composition, high toxicity, stable chemical structure and difficulty in being degraded by microorganisms. Therefore, the degradation of difficult-to-degrade organic wastewater has become an urgent problem to be solved in the field of contemporary environmental protection. Therefore, this article introduces an organic wastewater treatment agent that can degrade organic wastewater. Summary of the invention
[0004] The purpose of the present invention is to provide an organic wastewater treating agent and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] An organic wastewater treatment agent, which is prepared by reacting modified cellulose with functionalized nano-silicon dioxide;
[0006] The modified cellulose is prepared by reacting microcrystalline cellulose with thionyl chloride, N-(epoxypropyl)-N-phenyl-epoxyethylene methylamine and thiourea in sequence;
[0007] The functionalized nano-silica is prepared by reacting modified nano-silica with 2,4,6-triformylpyrogallol and 2,4-diamino-6-methoxypyrimidine;
[0008] The modified nano silicon dioxide is prepared by sequentially reacting nano silicon dioxide with silane coupling agent 4140, sodium periodate, p-phenylenediamine and dimethyl phosphite.
[0009] A method for preparing an organic wastewater treatment agent, the method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0010] (1) Nano-silica, silane coupling agent 4140 and isopropanol are mixed in a mass ratio of 8-12:1:30-50, stirred at 85-95°C and 200-300 r / min for 5-7 hours, centrifuged to obtain a solid, washed with deionized water for 3-5 times, and dried at 90-100°C for 2-4 hours to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water are mixed in a mass ratio of 1-2:1.9-2.1:95 ~105, stirred at 50~60r / min for 6~8min, stored at 20~30℃ in the dark for 70~74h, centrifuged, washed with deionized water for 3~5 times, vacuum dried at -10~0℃ for 22~26h to obtain aldehyded nano-silica; aldehyded nano-silica, ethanol and glacial acetic acid were mixed in a mass ratio of 1:20~30:0.4~0.5, and heated at 70~76℃, 200~300r / min, and nitrogen protection was used. , stirring for 10 to 14 minutes, adding p-phenylenediamine 2 to 3 times the mass of formaldehyded nano-silica at a uniform speed within 8 to 10 minutes, continuing stirring for 5 to 7 hours, filtering, washing with deionized water 3 to 5 times, and vacuum drying at 70 to 90°C for 10 to 14 hours to obtain pre-modified nano-silica; mixing the pre-modified nano-silica and methanol at a mass ratio of 1:20 to 30, stirring at 200 to 300 r / min under nitrogen protection for 10 to 14 minutes. n, adding a dimethyl phosphite mixed solution of 2 to 3 times the mass of the pre-modified nano-silica at a uniform speed within 8 to 10 minutes, heating to 60 to 64°C, stirring for 6 to 8 hours, filtering, washing with methanol for 3 to 5 times, and vacuum drying at 60 to 80°C for 10 to 14 hours to obtain modified nano-silica; mixing 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, modified nano-silica and solvent in a mass ratio of 1.2 to 1.4:
[0011] 1.6-1.8:2-3:10-20, add acetic acid solution with a volume of 0.16-0.17 times of the solvent, ultrasonicate for 15-25 minutes, place in a polytetrafluoroethylene reactor liner, stand at 110-130°C for 70-74 hours, centrifuge, wash with ethanol for 5-7 times, dry at 50-70°C for 10-14 hours, and obtain functionalized nano-silica;
[0012] (2) Mix cellulose and N,N-dimethylformamide in a mass ratio of 1:18-20, stir for 3-5 minutes at 85-95°C and 250-350 r / min, add 5.6-6 times the mass of microcrystalline cellulose of thionyl chloride within 8-10 minutes, continue stirring for 2-3 hours, pour into deionized water, stir at 200-300 r / min for 10-16 minutes, filter, wash with 2.8-3.2% ammonia water and deionized water alternately until neutral, and vacuum dry at 45-55°C for 11-13 hours to obtain chlorocellulose; Mix chlorocellulose and N-(epoxypropyl)-N-phenyl-oxirane methylamine in a mass ratio of 1:18-20, stir for 3-5 minutes, add thionyl chloride in an amount of 5.6-6 times the mass of microcrystalline cellulose within 8-10 minutes, continue stirring for 2-3 hours, pour into deionized water, stir at 200-300 r / min for 10-16 minutes, filter, wash with 2.8-3.2% ammonia water and deionized water alternately until neutral, and vacuum dry at 45-55°C for 11-13 hours to obtain chlorocellulose; 5-7:1-2, immersed in N-methylpyrrolidone, reacted at 200-300r / min, 70-90°C for 10-14h, vacuum dried at -10-0°C for 20-24h, washed with ether 3-5 times, vacuum dried at -10-0°C for 22-24h to obtain pre-modified cellulose; pre-modified cellulose, N,N-dimethylformamide and thiourea were mixed in a mass ratio of 1:20-30:0.4-0.6, stirred at 60-80°C, 200-300r / min for 46-50h, filtered, washed with deionized water 5-7 times, vacuum dried at 50-70°C for 22-24h to obtain modified cellulose;
[0013] (3) Modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica are mixed in a mass ratio of 4-6:1:4-6:0.4-0.6:18-20:2-4, stirred at 20-40°C and 200-300 r / min for 12-16 h, added with a catalyst 2-4 times the mass of TEMPO, continued to react for 12-16 h, filtered, washed with deionized water 3-5 times, and vacuum dried at -10-0°C for 22-24 h to obtain an organic wastewater treatment agent.
[0014] As an optimization, the solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1.
[0015] As an optimization, the concentration of the acetic acid solution in step (1) is 3M.
[0016] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0017] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0018] As an optimization, the mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring for 10 to 14 hours at 50 to 70°C, 200 to 300 r / min, and under argon protection.
[0019] As an optimization, the citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0020] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 11-12:46-47:0.017-0.019.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] When preparing the organic wastewater treatment agent, the present invention sequentially reacts nano silicon dioxide with silane coupling agent 4140, sodium periodate, p-phenylenediamine and dimethyl phosphite to obtain modified nano silicon dioxide; the modified nano silicon dioxide is reacted with 2,4,6-triformylpyrogallol and 2,4-diamino-6-methoxypyrimidine to obtain functionalized nano silicon dioxide; microcrystalline cellulose is sequentially reacted with thionyl chloride, N-(epoxypropyl)-N-phenyl-epoxyethanemethylamine and thiourea to obtain modified cellulose; and the modified cellulose is reacted with the functionalized nano silicon dioxide to obtain the organic wastewater treatment agent.
[0023] First, nano-silica is reacted with silane coupling agent 4140, sodium periodate, p-phenylenediamine and dimethyl phosphite in sequence to obtain modified nano-silica; modified nano-silica is reacted with 2,4,6-triformylpyrogallol and 2,4-diamino-6-methoxypyrimidine to obtain functionalized nano-silica; nano-silica is reacted with silane coupling agent 4140 and then oxidized with sodium periodate to obtain aldehyde-modified nano-silica, aldehyde-modified nano-silica reacts with p-phenylenediamine to generate Schiff base, and Schiff base can react with dimethyl phosphite. Under acidic conditions, phosphite will hydrolyze to generate phosphate anions, which can well adsorb cationic pollutants, and modified nano-silica reacts with 2,4,6-triformylpyrogallol and 2,4-diamino-6-methoxypyrimidine to generate organic frameworks, which can degrade organic pollutants under photocatalysis.
[0024] Secondly, the microcrystalline cellulose is reacted with thionyl chloride, N-(epoxypropyl)-N-phenyl-oxiranemethylamine and thiourea in sequence to obtain modified cellulose; the modified cellulose is reacted with functionalized nano-silica to obtain an organic wastewater treatment agent, the microcrystalline cellulose is reacted with thionyl chloride to generate chlorocellulose, the chlorocellulose is reacted with N-(epoxypropyl)-N-phenyl-oxiranemethylamine to generate quaternary ammonium salt, the quaternary ammonium salt can well adsorb anionic pollutants, and the epoxy group on N-(epoxypropyl)-N-phenyl-oxiranemethylamine can react with thiourea, thiourea can destroy the cell wall and cell membrane of the pathogen, making it lose its viability, and can also inhibit the metabolic process of the pathogen, thereby achieving a bactericidal effect. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Embodiment 1:
[0027] A method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0028] (1) Nano-silica, silane coupling agent 4140 and isopropanol were mixed in a mass ratio of 8:1:30, stirred at 85°C and 200 r / min for 5 h, centrifuged to obtain a solid, washed three times with deionized water, and dried at 90°C for 2 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water were mixed in a mass ratio of 1:1.9:95, stirred at 50 r / min for 6 min, and dried at 20°C. The mixture was stored in the dark for 70 h, centrifuged, washed with deionized water for 3 times, and vacuum dried at -10°C for 22 h to obtain formaldehyde-modified nano-silica. The formaldehyde-modified nano-silica, ethanol, and glacial acetic acid were mixed in a mass ratio of 1:20:0.4, stirred for 10 min at 70°C, 200 r / min, and under nitrogen protection. Within 8 min, p-phenylenediamine in an amount twice the mass of the formaldehyde-modified nano-silica was added at a uniform speed, and stirring was continued for 5 h. The mixture was filtered and washed with deionized water. 3 times, vacuum dried at 70°C for 10h to obtain pre-modified nano-silica; pre-modified nano-silica and methanol were mixed at a mass ratio of 1:20, stirred at 200r / min, nitrogen protection for 10min, and a dimethyl phosphite mixed solution twice the mass of the pre-modified nano-silica was uniformly added within 8min, the temperature was raised to 60°C, stirring was continued for 6h, filtered, washed with methanol 3 times, and vacuum dried at 60°C for 10h to obtain modified Nano-silica; 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, modified nano-silica and solvent were mixed in a mass ratio of 1.2:1.6:2:10, an acetic acid solution with a volume of 0.16 times of the solvent was added, ultrasonicated for 15 minutes, placed in a polytetrafluoroethylene reactor liner, allowed to stand at 110°C for 70 hours, centrifuged, washed with ethanol for 5 times, and dried at 50°C for 10 hours to obtain functionalized nano-silica;
[0029] (2) Cellulose and N,N-dimethylformamide were mixed in a mass ratio of 1:18, stirred at 85°C and 250 r / min for 3 min, 5.6 times the mass of microcrystalline cellulose of thionyl chloride was added within 8 min, stirring was continued for 2 h, poured into deionized water, stirred at 200 r / min for 10 min, filtered, washed alternately with 2.8% ammonia water and deionized water until neutral, and vacuum dried at 45°C for 11 h to obtain chlorocellulose; chlorocellulose and N-(epoxypropyl)-N-phenyl-epoxy Ethanemethylamine was mixed in a mass ratio of 5:1, immersed in N-methylpyrrolidone, reacted at 200 r / min and 70°C for 10 h, vacuum dried at -10°C for 20 h, washed with ether 3 times, and vacuum dried at -10°C for 22 h to obtain pre-modified cellulose; pre-modified cellulose, N,N-dimethylformamide and thiourea were mixed in a mass ratio of 1:20:0.4, stirred at 60°C and 200 r / min for 46 h, filtered, washed with deionized water 5 times, and vacuum dried at 50°C for 22 h to obtain modified cellulose;
[0030] (3) Modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica were mixed in a mass ratio of 4:1:4:0.4:18:2, stirred at 20°C and 200 r / min for 12 h, and a catalyst twice the mass of TEMPO was added. The reaction was continued for 12 h, filtered, washed three times with deionized water, and vacuum dried at -10°C for 22 h to obtain an organic wastewater treatment agent.
[0031] As an optimization, the solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1.
[0032] As an optimization, the concentration of the acetic acid solution in step (1) is 3M.
[0033] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0034] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0035] As an optimization, the mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring for 10 hours at 50°C, 200 r / min, under argon protection.
[0036] As an optimization, the citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0037] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 11:46:0.017.
[0038] Embodiment 2:
[0039] A method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0040] (1) Nano-silica, silane coupling agent 4140 and isopropanol were mixed in a mass ratio of 10:1:40, stirred at 90°C and 250 r / min for 6 h, centrifuged to obtain a solid, washed with deionized water for 4 times, and dried at 95°C for 3 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water were mixed in a mass ratio of 1.5:2:100, stirred at 55 r / min for 7 min, and dried at 25°C. The mixture was stored in the dark for 72 hours, centrifuged, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain formaldehyde-modified nano-silica. The formaldehyde-modified nano-silica, ethanol and glacial acetic acid were mixed in a mass ratio of 1:25:0.45, stirred for 12 minutes at 73°C, 250 r / min, and under nitrogen protection. Within 9 minutes, p-phenylenediamine, which was 2.5 times the mass of the formaldehyde-modified nano-silica, was added at a uniform speed, and stirring was continued for 6 hours. The mixture was filtered and washed with deionized water. 4 times, vacuum dried at 80°C for 12h to obtain pre-modified nano-silica; pre-modified nano-silica and methanol were mixed at a mass ratio of 1:25, stirred at 250r / min, under nitrogen protection for 12min, and a mixed solution of dimethyl phosphite 2.5 times the mass of the pre-modified nano-silica was uniformly added within 9min, the temperature was raised to 62°C, stirring was continued for 7h, filtered, washed with methanol 4 times, and vacuum dried at 70°C for 12h to obtain modified nano-silica. 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, modified nano-silica and solvent were mixed in a mass ratio of 1.3:1.7:2.5:15, an acetic acid solution with a volume of 0.165 times of the solvent was added, ultrasonicated for 20 minutes, placed in a polytetrafluoroethylene reactor liner, allowed to stand at 120°C for 72 hours, centrifuged, washed with ethanol for 6 times, and dried at 60°C for 12 hours to obtain functionalized nano-silica;
[0041] (2) Cellulose and N,N-dimethylformamide were mixed in a mass ratio of 1:19, stirred at 90°C and 300 r / min for 4 min, 5.8 times the mass of microcrystalline cellulose of thionyl chloride was added within 9 min, stirring was continued for 2.5 h, poured into deionized water, stirred at 250 r / min for 13 min, filtered, washed alternately with 3% ammonia water and deionized water until neutral, and vacuum dried at 50°C for 12 h to obtain chlorocellulose; chlorocellulose and N-(epoxypropyl)-N-phenyl-epoxy Ethane methylamine was mixed in a mass ratio of 6:1.5, immersed in N-methylpyrrolidone, reacted at 250r / min and 80°C for 12h, vacuum dried at -5°C for 22h, washed with ether 4 times, and vacuum dried at -5°C for 23h to obtain pre-modified cellulose; pre-modified cellulose, N,N-dimethylformamide and thiourea were mixed in a mass ratio of 1:25:0.5, stirred at 70°C and 250r / min for 48h, filtered, washed with deionized water 6 times, and vacuum dried at 60°C for 23h to obtain modified cellulose;
[0042] (3) Modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica were mixed in a mass ratio of 5:1:5:0.5:19:3, stirred at 30°C and 250 r / min for 14 h, and a catalyst 3 times the mass of TEMPO was added. The reaction was continued for 14 h, filtered, washed with deionized water 4 times, and vacuum dried at -5°C for 23 h to obtain an organic wastewater treatment agent.
[0043] As an optimization, the solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1.
[0044] As an optimization, the concentration of the acetic acid solution in step (1) is 3M.
[0045] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0046] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0047] As an optimization, the mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring for 12 hours at 60°C, 250 r / min, under argon protection.
[0048] As an optimization, the citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0049] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 11.5:46.5:0.018.
[0050] Embodiment 3:
[0051] A method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0052] (1) Nano-silica, silane coupling agent 4140 and isopropanol were mixed in a mass ratio of 12:1:50, stirred at 95°C and 300 r / min for 7 h, centrifuged to obtain a solid, washed with deionized water for 5 times, and dried at 100°C for 4 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water were mixed in a mass ratio of 2:2.1:105, stirred at 60 r / min for 8 min, and dried at 30 ℃ and protected from light for 74h, centrifuged, washed with deionized water for 5 times, and vacuum dried at 0℃ for 26h to obtain formaldehyde-modified nano-silica; mixed formaldehyde-modified nano-silica, ethanol and glacial acetic acid in a mass ratio of 1:30:0.5, stirred for 14min at 76℃, 300r / min, and nitrogen protection, and added p-phenylenediamine 3 times the mass of formaldehyde-modified nano-silica at a uniform speed within 10min, continued stirring for 7h, filtered, and washed with deionized water. The pre-modified nano-silica was prepared by washing 5 times and vacuum drying at 90°C for 14 hours; the pre-modified nano-silica and methanol were mixed at a mass ratio of 1:30, stirred at 300r / min, under nitrogen protection for 14 minutes, and a dimethyl phosphite mixed solution 3 times the mass of the pre-modified nano-silica was uniformly added within 10 minutes, the temperature was raised to 64°C, stirring was continued for 8 hours, filtered, washed with methanol 5 times, and vacuum dried at 80°C for 14 hours to obtain the modified nano-silica. Functionalized nano-silica; 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, modified nano-silica and solvent were mixed in a mass ratio of 1.4:1.8:3:20, an acetic acid solution with a volume of 0.17 times that of the solvent was added, ultrasonicated for 25 minutes, placed in a polytetrafluoroethylene reactor liner, allowed to stand at 130°C for 74 hours, centrifuged, washed with ethanol for 7 times, and dried at 70°C for 14 hours to obtain functionalized nano-silica;
[0053] (2) Cellulose and N,N-dimethylformamide were mixed in a mass ratio of 1:20, stirred at 95°C and 350 r / min for 5 min, thionyl chloride 6 times the mass of microcrystalline cellulose was added within 10 min, stirring was continued for 3 h, poured into deionized water, stirred at 300 r / min for 16 min, filtered, washed alternately with 3.2% ammonia water and deionized water until neutral, and vacuum dried at 55°C for 13 h to obtain chlorocellulose; chlorocellulose and N-(epoxypropyl)-N-phenyl-cyclohexyl Ethylene oxide and methylamine were mixed in a mass ratio of 7:2, immersed in N-methylpyrrolidone, reacted at 300 r / min and 90°C for 14 hours, vacuum dried at 0°C for 24 hours, washed with ether for 5 times, and vacuum dried at 0°C for 24 hours to obtain pre-modified cellulose; pre-modified cellulose, N,N-dimethylformamide and thiourea were mixed in a mass ratio of 1:30:0.6, stirred at 80°C and 300 r / min for 50 hours, filtered, washed with deionized water for 7 times, and vacuum dried at 70°C for 24 hours to obtain modified cellulose;
[0054] (3) Modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica were mixed in a mass ratio of 6:1:6:0.6:20:4, stirred at 40°C and 300 r / min for 16 h, and a catalyst 4 times the mass of TEMPO was added. The reaction was continued for 16 h, filtered, washed with deionized water 5 times, and vacuum dried at 0°C for 24 h to obtain an organic wastewater treatment agent.
[0055] As an optimization, the solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1.
[0056] As an optimization, the concentration of the acetic acid solution in step (1) is 3M.
[0057] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0058] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0059] As an optimization, the mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring at 70°C, 300 r / min, under argon protection, for 14 hours.
[0060] As an optimization, the citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0061] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 12:47:0.019.
[0062] Comparative Example 1:
[0063] A method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0064] (1) Nano-silica, silane coupling agent 4140 and isopropanol were mixed in a mass ratio of 10:1:40, stirred at 90°C and 250 r / min for 6 h, centrifuged to obtain a solid, washed with deionized water for 4 times, and dried at 95°C for 3 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water were mixed in a mass ratio of 1.5:2:100, stirred at 55 r / min for 7 min, stored in the dark at 25°C for 72 h, centrifuged, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 h to obtain aldehyde-modified nano-silica; aldehyde-modified nano-silica, ethanol and glacial acetic acid were mixed in a mass ratio of 1:25:0.45, and stirred at 73°C and 250 r / min for 7 min. min, under nitrogen protection, stirred for 12 min, and within 9 min, p-phenylenediamine 2.5 times the mass of formaldehyded nano-silica was uniformly added, and stirring was continued for 6 h, filtered, washed with deionized water 4 times, and vacuum dried at 80 ° C for 12 h to obtain pre-modified nano-silica; 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, pre-modified nano-silica and solvent were mixed in a mass ratio of 1.3:1.7:2.5:15, and acetic acid solution 0.165 times the volume of the solvent was added, ultrasonicated for 20 min, placed in a polytetrafluoroethylene reactor liner, stood at 120 ° C for 72 h, centrifuged, washed with ethanol 6 times, and dried at 60 ° C for 12 h to obtain functionalized nano-silica;
[0065] (2) Cellulose and N,N-dimethylformamide were mixed in a mass ratio of 1:19, stirred at 90°C and 300 r / min for 4 min, 5.8 times the mass of microcrystalline cellulose of thionyl chloride was added within 9 min, stirring was continued for 2.5 h, poured into deionized water, stirred at 250 r / min for 13 min, filtered, washed alternately with 3% ammonia water and deionized water until neutral, and vacuum dried at 50°C for 12 h to obtain chlorocellulose; chlorocellulose and N-(epoxypropyl)-N-phenyl-epoxy Ethane methylamine was mixed in a mass ratio of 6:1.5, immersed in N-methylpyrrolidone, reacted at 250r / min and 80°C for 12h, vacuum dried at -5°C for 22h, washed with ether 4 times, and vacuum dried at -5°C for 23h to obtain pre-modified cellulose; pre-modified cellulose, N,N-dimethylformamide and thiourea were mixed in a mass ratio of 1:25:0.5, stirred at 70°C and 250r / min for 48h, filtered, washed with deionized water 6 times, and vacuum dried at 60°C for 23h to obtain modified cellulose;
[0066] (3) Modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica were mixed in a mass ratio of 5:1:5:0.5:19:3, stirred at 30°C and 250 r / min for 14 h, and a catalyst 3 times the mass of TEMPO was added. The reaction was continued for 14 h, filtered, washed with deionized water 4 times, and vacuum dried at -5°C for 23 h to obtain an organic wastewater treatment agent.
[0067] As an optimization, the solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1.
[0068] As an optimization, the concentration of the acetic acid solution in step (1) is 3M.
[0069] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0070] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0071] As an optimization, the mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring for 12 hours at 60°C, 250 r / min, under argon protection.
[0072] As an optimization, the citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0073] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 11.5:46.5:0.018.
[0074] Comparative Example 2
[0075] A method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0076] (1) Nano-silica, silane coupling agent 4140 and isopropanol were mixed in a mass ratio of 10:1:40, stirred at 90°C and 250 r / min for 6 h, centrifuged to separate the solid, washed with deionized water for 4 times, and dried at 95°C for 3 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water were mixed in a mass ratio of 1.5:2:100, stirred at 55 r / min for 7 min, stored in the dark at 25°C for 72 h, centrifuged, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 h to obtain aldehyde-modified nano-silica; aldehyde-modified nano-silica, ethanol and glacial acetic acid were mixed in a mass ratio of 1:25:0.45, stirred at 7 3℃, 250r / min, under nitrogen protection, stir for 12min, add p-phenylenediamine 2.5 times the mass of formaldehyded nano-silica at a uniform speed within 9min, continue stirring for 6h, filter, wash with deionized water 4 times, vacuum dry at 80℃ for 12h, and obtain pre-modified nano-silica; mix pre-modified nano-silica and methanol in a mass ratio of 1:25, stir for 12min at 250r / min, under nitrogen protection, add dimethyl phosphite mixed solution 2.5 times the mass of pre-modified nano-silica at a uniform speed within 9min, heat to 62℃, continue stirring for 7h, filter, wash with methanol 4 times, vacuum dry at 70℃ for 12h, and obtain modified nano-silica;
[0077] (2) Cellulose and N,N-dimethylformamide were mixed in a mass ratio of 1:19, stirred at 90°C and 300 r / min for 4 min, 5.8 times the mass of microcrystalline cellulose of thionyl chloride was added within 9 min, stirring was continued for 2.5 h, poured into deionized water, stirred at 250 r / min for 13 min, filtered, washed alternately with 3% ammonia water and deionized water until neutral, and vacuum dried at 50°C for 12 h to obtain chlorocellulose; chlorocellulose and N-(epoxypropyl)-N-phenyl-epoxy Ethane methylamine was mixed in a mass ratio of 6:1.5, immersed in N-methylpyrrolidone, reacted at 250r / min and 80°C for 12h, vacuum dried at -5°C for 22h, washed with ether 4 times, and vacuum dried at -5°C for 23h to obtain pre-modified cellulose; pre-modified cellulose, N,N-dimethylformamide and thiourea were mixed in a mass ratio of 1:25:0.5, stirred at 70°C and 250r / min for 48h, filtered, washed with deionized water 6 times, and vacuum dried at 60°C for 23h to obtain modified cellulose;
[0078] (3) Modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and modified nano-silica were mixed in a mass ratio of 5:1:5:0.5:19:3, stirred at 30°C and 250 r / min for 14 h, and a catalyst 3 times the mass of TEMPO was added. The reaction was continued for 14 h, filtered, washed with deionized water 4 times, and vacuum dried at -5°C for 23 h to obtain an organic wastewater treatment agent.
[0079] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0080] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0081] As an optimization, the mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring for 12 hours at 60°C, 250 r / min, under argon protection.
[0082] As an optimization, the citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0083] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 11.5:46.5:0.018.
[0084] Comparative Example 3
[0085] A method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0086] (1) Nano-silica, silane coupling agent 4140 and isopropanol were mixed in a mass ratio of 10:1:40, stirred at 90°C and 250 r / min for 6 h, centrifuged to obtain a solid, washed with deionized water for 4 times, and dried at 95°C for 3 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water were mixed in a mass ratio of 1.5:2:100, stirred at 55 r / min for 7 min, and dried at 25°C. The mixture was stored in the dark for 72 hours, centrifuged, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain formaldehyde-modified nano-silica. The formaldehyde-modified nano-silica, ethanol and glacial acetic acid were mixed in a mass ratio of 1:25:0.45, stirred for 12 minutes at 73°C, 250 r / min, and under nitrogen protection. Within 9 minutes, p-phenylenediamine, which was 2.5 times the mass of the formaldehyde-modified nano-silica, was added at a uniform speed, and stirring was continued for 6 hours. The mixture was filtered and washed with deionized water. 4 times, vacuum dried at 80°C for 12h to obtain pre-modified nano-silica; pre-modified nano-silica and methanol were mixed at a mass ratio of 1:25, stirred at 250r / min, under nitrogen protection for 12min, and a mixed solution of dimethyl phosphite 2.5 times the mass of the pre-modified nano-silica was uniformly added within 9min, the temperature was raised to 62°C, stirring was continued for 7h, filtered, washed with methanol 4 times, and vacuum dried at 70°C for 12h to obtain modified nano-silica. 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, modified nano-silica and solvent were mixed in a mass ratio of 1.3:1.7:2.5:15, an acetic acid solution with a volume of 0.165 times of the solvent was added, ultrasonicated for 20 minutes, placed in a polytetrafluoroethylene reactor liner, allowed to stand at 120°C for 72 hours, centrifuged, washed with ethanol for 6 times, and dried at 60°C for 12 hours to obtain functionalized nano-silica;
[0087] (2) Cellulose was mixed with N,N-dimethylformamide in a mass ratio of 1:19, stirred at 90°C and 300 r / min for 4 min, thionyl chloride 5.8 times the mass of microcrystalline cellulose was added within 9 min, stirring was continued for 2.5 h, poured into deionized water, stirred at 250 r / min for 13 min, filtered, washed alternately with 3% ammonia water and deionized water until neutral, and vacuum dried at 50°C for 12 h to obtain chlorocellulose; chlorocellulose and N-(epoxypropyl)-N-phenyl-oxirane methylamine were mixed in a mass ratio of 6:1.5, immersed in N-methylpyrrolidone, reacted at 250 r / min and 80°C for 12 h, vacuum dried at -5 for 22 h, washed with ether 4 times, and vacuum dried at -5°C for 23 h to obtain pre-modified cellulose;
[0088] (3) Pre-modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica were mixed in a mass ratio of 5:1:5:0.5:19:3, stirred at 30°C and 250 r / min for 14 h, and a catalyst 3 times the mass of TEMPO was added. The reaction was continued for 14 h, filtered, washed with deionized water 4 times, and vacuum dried at -5°C for 23 h to obtain an organic wastewater treatment agent.
[0089] As an optimization, the solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1.
[0090] As an optimization, the concentration of the acetic acid solution in step (1) is 3M.
[0091] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0092] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0093] As an optimization, the mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring for 12 hours at 60°C, 250 r / min, under argon protection.
[0094] As an optimization, the citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0095] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 11.5:46.5:0.018.
[0096] Comparative Example 4
[0097] A method for preparing an organic wastewater treatment agent mainly comprises the following preparation steps:
[0098] (1) Nano-silica, silane coupling agent 4140 and isopropanol were mixed in a mass ratio of 10:1:40, stirred at 90°C and 250 r / min for 6 h, centrifuged to obtain a solid, washed with deionized water for 4 times, and dried at 95°C for 3 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water were mixed in a mass ratio of 1.5:2:100, stirred at 55 r / min for 7 min, and dried at 25°C. The mixture was stored in the dark for 72 hours, centrifuged, washed with deionized water for 4 times, and vacuum dried at -5°C for 24 hours to obtain formaldehyde-modified nano-silica. The formaldehyde-modified nano-silica, ethanol and glacial acetic acid were mixed in a mass ratio of 1:25:0.45, stirred for 12 minutes at 73°C, 250 r / min, and under nitrogen protection. Within 9 minutes, p-phenylenediamine, which was 2.5 times the mass of the formaldehyde-modified nano-silica, was added at a uniform speed, and stirring was continued for 6 hours. The mixture was filtered and washed with deionized water. 4 times, vacuum dried at 80°C for 12h to obtain pre-modified nano-silica; pre-modified nano-silica and methanol were mixed at a mass ratio of 1:25, stirred at 250r / min, under nitrogen protection for 12min, and a mixed solution of dimethyl phosphite 2.5 times the mass of the pre-modified nano-silica was uniformly added within 9min, the temperature was raised to 62°C, stirring was continued for 7h, filtered, washed with methanol 4 times, and vacuum dried at 70°C for 12h to obtain modified nano-silica. 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, modified nano-silica and solvent were mixed in a mass ratio of 1.3:1.7:2.5:15, an acetic acid solution with a volume of 0.165 times of the solvent was added, ultrasonicated for 20 minutes, placed in a polytetrafluoroethylene reactor liner, allowed to stand at 120°C for 72 hours, centrifuged, washed with ethanol for 6 times, and dried at 60°C for 12 hours to obtain functionalized nano-silica;
[0099] (2) Cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica were mixed in a mass ratio of 5:1:5:0.5:19:3, stirred at 30°C and 250 r / min for 14 h, and a catalyst 3 times the mass of TEMPO was added. The reaction was continued for 14 h, filtered, washed with deionized water 4 times, and vacuum dried at -5°C for 23 h to obtain an organic wastewater treatment agent.
[0100] As an optimization, the solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:1.
[0101] As an optimization, the concentration of the acetic acid solution in step (1) is 3M.
[0102] As an optimization, the specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
[0103] As an optimization, the cellulose in step (2) is microcrystalline cellulose.
[0104] As an optimization, the mixed solution in step (2) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring for 12 hours at 60°C, 250 r / min, under argon protection.
[0105] As an optimization, the citric acid buffer in step (2) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution to a pH of 5.
[0106] As an optimization, the catalyst in step (3) is prepared by uniformly mixing L-proline, the mixed solution and deionized water in a mass ratio of 11.5:46.5:0.018.
[0107] Test Example 1:
[0108] Antimicrobial testing
[0109] The test was carried out according to the GB / T20944 oscillation method, wherein the selected bacteria species were Staphylococcus aureus and Escherichia coli. The results are shown in Table 1.
[0110] Table 1
[0111]
[0112] From the comparison of the experimental data in Table 1, it can be found that the organic wastewater treatment agent prepared by the present invention has good antibacterial ability.
[0113] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 1, it can be found that the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 3, indicating that the epoxy group on N-(epoxypropyl)-N-phenyl-oxirane methylamine can react with thiourea, and thiourea can destroy the cell wall and cell membrane of the pathogen, making it lose its viability, and can also inhibit the metabolic process of the pathogen, thereby achieving a bactericidal effect;
[0114] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 1, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 4, which shows that quaternary ammonium salts can change the permeability of cells and rupture the bacteria; can denature proteins; can inhibit certain enzymes in bacteria and make them inactive; and because of their good surface activity, they can accumulate at high concentrations on the surface of bacteria, affecting the metabolism of bacteria, thereby achieving a bactericidal effect.
[0115] Test Example 2:
[0116] Anionic pollutants, anionic pollutant adsorption test
[0117] Test method: The measuring equipment is Shimadzu UV-2700 ultraviolet spectrophotometer of NEC Corporation. The process is as follows: prepare 10 mg / L Congo red solution and Rhodium B solution respectively; put the sewage treatment agent into a sandwich beaker, and pour in Congo red solution 20 times the mass of the sewage treatment agent, let it stand in the dark for 120 minutes, and calculate the adsorption rate of Congo red and Rhodium B, where Congo red adsorption rate = (Congo red initial absorbance value - Congo red 120min absorbance value) / Congo red initial absorbance value * 100%, and Rhodium B is the same. The results are shown in Table 2.
[0118] Table 2
[0119] Congo Red Luo Mingdan B Example 1 65.3% 64.7% Example 2 64.9% 65.1% Example 3 65.4% 65.2% Comparative Example 1 65.2% 13.5% Comparative Example 2 64.8% 64.9% Comparative Example 3 65.0% 65.3% Comparative Example 4 12.7% 64.6%
[0120] From the comparison of the experimental data in Table 2, it can be found that the organic wastewater treatment agent prepared by the present invention has good anionic pollutants and anionic pollutant adsorption capacity.
[0121] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 2, it can be found that the Congo red adsorption rate of Examples 1, 2, 3 is higher than that of Comparative Example 4, which indicates that the microcrystalline cellulose reacts with thionyl chloride to generate chlorocellulose, and the chlorocellulose reacts with N-(epoxypropyl)-N-phenyl-ethylene oxide methylamine to generate quaternary ammonium salt, and the quaternary ammonium salt can adsorb anionic pollutants well;
[0122] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the adsorption rate of rhodium B in Examples 1, 2, 3 is higher than that in Comparative Example 1, which indicates that the nano-silica is reacted with the silane coupling agent 4140 and then oxidized with sodium periodate to obtain the aldehyde-modified nano-silica, and the aldehyde-modified nano-silica reacts with p-phenylenediamine to generate a Schiff base, which can react with dimethyl phosphite. Under acidic conditions, the phosphite will hydrolyze to generate phosphate anions, which can well adsorb cationic pollutants.
[0123] Test Example 3
[0124] Organic pollutant degradation test
[0125] Test method: The measuring equipment is Shimadzu UV-2700 ultraviolet spectrophotometer of JEOL Ltd. The process is as follows: prepare 10 mg / L Congo red solution and Rhodium B solution respectively; put the sewage treatment agent into a sandwich beaker, and pour in Congo red solution 20 times the mass of the sewage treatment agent, let it stand for 120 minutes under natural light, and calculate the degradation rate of Congo red and Rhodium B, where Congo red degradation rate = (Congo red initial absorbance value - Congo red 120min absorbance value) / Congo red initial absorbance value * 100%, and Rhodium B is the same. The results are shown in Table 3.
[0126] Table 3
[0127] Congo Red Luo Mingdan B Example 1 99.5% 99.4% Example 2 99.2% 99.6% Example 3 99.3% 99.3% Comparative Example 1 99.1% 92.9% Comparative Example 2 64.5% 64.7% Comparative Example 3 99.4% 99.4% Comparative Example 4 93.1% 99.1%
[0128] From the comparison of the experimental data in Table 3, it can be found that the organic wastewater treatment agent prepared by the present invention has good pollutant degradation ability.
[0129] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 3, it can be found that the degradation rates of Congo red and rhodamine B in Examples 1, 2, and 3 are higher than those in Comparative Example 2, indicating that the functionalized nano-silica generates an organic framework that can degrade organic pollutants under photocatalysis;
[0130] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the degradation rate of Rhodiola B in Examples 1, 2, 3 is higher than that in Comparative Example 1, which indicates that the nano-silica reacts with the silane coupling agent 4140 and then is oxidized by sodium periodate to obtain aldehyde-modified nano-silica, and the aldehyde-modified nano-silica reacts with p-phenylenediamine to generate Schiff base, which can react with dimethyl phosphite. Under acidic conditions, the phosphite will hydrolyze to generate phosphate anions, which can well adsorb cationic pollutants, thereby better degrading organic pollutants.
[0131] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the Congo red degradation rates of Examples 1, 2, 3 are higher than those of Comparative Example 4, which indicates that microcrystalline cellulose reacts with thionyl chloride to generate chlorocellulose, and chlorocellulose reacts with N-(epoxypropyl)-N-phenyl-ethylene oxide methylamine to generate quaternary ammonium salts, and quaternary ammonium salts can well adsorb anionic pollutants, thereby better degrading organic pollutants.
[0132] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An organic wastewater treatment agent, characterized in that: The organic wastewater treatment agent is prepared by reacting modified cellulose with functionalized nano-silicon dioxide; The modified cellulose is prepared by reacting microcrystalline cellulose with thionyl chloride, N-(epoxypropyl)-N-phenyl-epoxyethylene methylamine and thiourea in sequence; The functionalized nano-silica is prepared by reacting modified nano-silica with 2,4,6-triformylpyrogallol and 2,4-diamino-6-methoxypyrimidine; The modified nano silicon dioxide is prepared by sequentially reacting nano silicon dioxide with silane coupling agent 4140, sodium periodate, p-phenylenediamine and dimethyl phosphite.
2. A method for preparing an organic wastewater treatment agent, characterized in that: The preparation method of the organic wastewater treatment agent mainly includes the following preparation steps: (1) Nano-silica, silane coupling agent 4140 and isopropanol are mixed in a mass ratio of 8-12:1:30-50, stirred at 85-95°C and 200-300 r / min for 5-7 h, centrifuged to obtain a solid, washed with deionized water for 3-5 times, and dried at 90-100°C for 2-4 h to obtain hydroxylated nano-silica; hydroxylated nano-silica, sodium periodate and deionized water are mixed in a mass ratio of 1-2:1.9-2.1:95-105, stirred at 50-60 r / min for 6-8 min, and dried at 20- The mixture was stored at 30°C in the dark for 70 to 74 hours, centrifuged, washed with deionized water for 3 to 5 times, and vacuum dried at -10 to 0°C for 22 to 26 hours to obtain aldehyded nano-silica; the aldehyded nano-silica, ethanol and glacial acetic acid were mixed in a mass ratio of 1:20 to 30:0.4 to 0.5, stirred for 10 to 14 minutes at 70 to 76°C, 200 to 300 r / min, and nitrogen protection, and p-phenylenediamine in an amount of 2 to 3 times the mass of the aldehyded nano-silica was uniformly added within 8 to 10 minutes, the stirring was continued for 5 to 7 hours, filtered, and washed with deionized water. The pre-modified nano-silica was prepared by washing 3 to 5 times, vacuum drying at 70 to 90°C for 10 to 14 hours, and mixing the pre-modified nano-silica with methanol in a mass ratio of 1:20 to 30, stirring for 10 to 14 minutes at 200 to 300 r / min under nitrogen protection, and uniformly adding a dimethyl phosphite mixed solution 2 to 3 times the mass of the pre-modified nano-silica within 8 to 10 minutes, heating to 60 to 64°C, continuing to stir for 6 to 8 hours, filtering, washing with methanol 3 to 5 times, and vacuum drying at 60 to 80°C for 10 to 14 hours to obtain the modified nano-silica. Functionalized nano-silica; 2,4,6-triformylpyrogallol, 2,4-diamino-6-methoxypyrimidine, modified nano-silica and solvent are mixed in a mass ratio of 1.2-1.4:1.6-1.8:2-3:10-20, an acetic acid solution of 0.16-0.17 times the volume of the solvent is added, ultrasonicated for 15-25 minutes, placed in a polytetrafluoroethylene reactor liner, allowed to stand at 110-130°C for 70-74 hours, centrifuged, washed with ethanol for 5-7 times, and dried at 50-70°C for 10-14 hours to obtain functionalized nano-silica; (2) Mix cellulose and N,N-dimethylformamide in a mass ratio of 1:18-20, stir for 3-5 minutes at 85-95°C and 250-350 r / min, add 5.6-6 times the mass of microcrystalline cellulose of thionyl chloride within 8-10 minutes, continue stirring for 2-3 hours, pour into deionized water, stir at 200-300 r / min for 10-16 minutes, filter, wash with 2.8-3.2% ammonia water and deionized water alternately until neutral, and vacuum dry at 45-55°C for 11-13 hours to obtain chlorocellulose; Mix chlorocellulose and N-(epoxypropyl)-N-phenyl-oxirane methylamine in a mass ratio of 1:18-20, stir for 3-5 minutes, add thionyl chloride in an amount of 5.6-6 times the mass of microcrystalline cellulose within 8-10 minutes, continue stirring for 2-3 hours, pour into deionized water, stir at 200-300 r / min for 10-16 minutes, filter, wash with 2.8-3.2% ammonia water and deionized water alternately until neutral, and vacuum dry at 45-55°C for 11-13 hours to obtain chlorocellulose; 5-7:1-2, immersed in N-methylpyrrolidone, reacted at 200-300r / min, 70-90°C for 10-14h, vacuum dried at -10-0°C for 20-24h, washed with ether 3-5 times, vacuum dried at -10-0°C for 22-24h to obtain pre-modified cellulose; pre-modified cellulose, N,N-dimethylformamide and thiourea were mixed in a mass ratio of 1:20-30:0.4-0.6, stirred at 60-80°C, 200-300r / min for 46-50h, filtered, washed with deionized water 5-7 times, vacuum dried at 50-70°C for 22-24h to obtain modified cellulose; (3) Modified cellulose, TEMPO, laccase, mixed solution, citric acid buffer, and functionalized nano-silica are mixed in a mass ratio of 4-6:1:4-6:0.4-0.6:18-20:2-4, stirred at 20-40°C and 200-300 r / min for 12-16 h, added with a catalyst 2-4 times the mass of TEMPO, continued to react for 12-16 h, filtered, washed with deionized water 3-5 times, and vacuum dried at -10-0°C for 22-24 h to obtain an organic wastewater treatment agent.
3. The method for preparing an organic wastewater treatment agent according to claim 2, characterized in that: The solvent in step (1) is prepared by uniformly mixing mesitylene and 1,4-dioxane in a volume ratio of 1:
1.
4. The method for preparing an organic wastewater treatment agent according to claim 2, characterized in that: The concentration of the acetic acid solution in step (1) is 3M.
5. The method for preparing an organic wastewater treatment agent according to claim 2, characterized in that: The specific operation of the centrifugation in step (1) is centrifugation at a speed of 10000 rpm for 3 minutes.
6. The method for preparing an organic wastewater treatment agent according to claim 2, characterized in that: The cellulose in step (2) is microcrystalline cellulose.
7. The method for preparing an organic wastewater treatment agent according to claim 2, characterized in that: The mixed solution in step (3) is prepared by mixing lithium bis(trifluoromethanesulfonyl)imide and triethylene glycol dimethyl ether in a molar ratio of 1:1, and stirring at 50-70°C, 200-300 r / min, under argon protection, for 10-14 hours.
8. The method for preparing an organic wastewater treating agent according to claim 2, characterized in that: The citric acid buffer in step (3) is prepared by mixing 50 mM citric acid solution and 50 mM sodium citrate solution until the pH value is 5.
9. The method for preparing an organic wastewater treating agent according to claim 2, characterized in that: The catalyst in step (3) is prepared by uniformly mixing L-proline, mixed solution and deionized water in a mass ratio of 11-12:46-47:0.017-0.019.
Citation Information
Patent Citations
Cellulose quaternary ammonium salt adsorbing agent, and preparation method and application thereof
CN108404885A
Printing and dyeing wastewater treatment agent and preparation method thereof
CN112892503A
IN991MUN2001A
Cited By
Denitrification method for landfill leachate
CN120903778A
A method for denitrification of landfill leachate
CN120903778B